Comparison of the effects of nicardipine and remifentanil on surgical visual field and hemodynamic parameters in tympanomastoidectomy cases - Celal Saritoy; Erol Karaaslan; Ahmet Selim Ozkan; Mehmet Tan; Ilham Gulcek (Medicine Science)
In this study; We aimed to compare the surgical visual field and hemodynamic effects of Nicardipine and Remifentanil in microscopic tympanomastoidectomy patients. The study was planned as a prospective, double-blind, and randomized clinical trial. A total of 64 patients aged between 18 and 65 were included in the study and the patients were randomized into 2 groups: Group N (Nicardipine=32) and Group R (Remifentanil=32). The input data were measured at pre-induction (T0), 5 minutes post-incision (T1), 20 minutes post-incision (T2), mastoidectomy during the tour (T3), cholesteatoma clearance (T4), grafting (T5), extubation (T6), 10 minutes post-extubation (T7), at the time of admission to the post-anesthesia care unit (PACU) (T8) and the 15th minute (T9) in PACU along with hemodynamic parameters values. In the evaluation of the visibility of the surgical field, the Boezaart Scale was used. There was no significant difference in demographic data in both groups. Considering the hemodynamic parameters between the groups, HR values were higher in Group N during the whole period (T1-T9) (p [Med-Science 2024; 13(4.000): 854-60]